Epoxy resin surface alternate spraying embedded composite coating and preparation method thereof
By using epoxy resin surface to alternately spray the embedded composite coating on the surface of the resin-based composite material, combined with thermoplastic polyimide and nano-alumina powder, it is solved that the coating in the prior art is difficult to have both electrical insulation and burn resistance. The problem of corrosion has achieved a composite coating with high bonding strength and ablation resistance, which significantly improves the performance of the electromagnetic gun insulating support.
Patent Information
- Application Number
- CN202411567930.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art is difficult to prepare a ceramic thermal protection coating with both electrical insulation and ablation resistance on the surface of resin-based composite materials, resulting in the limitation of the life and service reliability of the electromagnetic gun insulating support.
The preparation method of alternately spraying the embedded composite coating on the surface of epoxy resin is used to form polyimide by mixing thermoplastic polyimide powder, thermoset polyimide powder and nano-alumina powder with a binder. NanoAl2O3 composite powder is sprayed alternately on resin-based composite materials using wide-speed domain high-energy plasma spraying technology to form a composite coating with high binding strength and ablation resistance.
The composite coating has high bonding strength and ablation resistance, with a resistivity of 71TΩ·cm, and a bending strength of 235 MPa after 150 ablations, which significantly improves the mechanical properties and ablation resistance of the insulating support.
Smart Images

Figure CN119410014A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite coating preparation, and relates to an epoxy resin surface alternately sprayed embedded composite coating and a preparation method thereof. Background Art
[0002] Electromagnetic guns break through the speed and energy limits of mechanical and chemical energy launches by converting electromagnetic energy into the instantaneous kinetic energy required to launch the payload. It is a new concept kinetic weapon. The electromagnetic railgun mainly includes a barrel, an aluminum armature and a power supply. The barrel is mainly composed of a copper alloy rail, an insulating support and an outer cladding. Among them, the insulating support plays the role of supporting the rail and ensuring the electrical insulation between the rails. The combined effect of high-temperature plasma ablation and aluminum liquid ablation will cause the strength and insulation performance of the support to decrease, thereby causing the entire system to fail. Ceramic materials are difficult to use as support structure materials due to their low toughness and poor reliability. At present, the insulating support usually uses resin-based composite materials with high specific strength, good fatigue fracture resistance and corrosion resistance. However, its poor high temperature resistance, ablation resistance and erosion resistance are important reasons that restrict the life of the electromagnetic gun barrel. Improving the mechanical properties and ablation resistance of the insulating support is of great significance to improving the performance and efficiency of the electromagnetic launch system.
[0003] On the basis of improving the temperature resistance of the resin-based composite material itself, a thermal protective coating is prepared on the surface of the resin base to meet the extreme working conditions of the electromagnetic railgun. Due to the low decomposition temperature of epoxy resin-based composite materials, high requirements are placed on the coating preparation process. The current mainstream technologies include chemical vapor deposition (CVD), physical vapor deposition (PVD), sol-gel, cold spraying, and thermal spraying. However, it is difficult to prepare high-quality coatings on the surface of oversized parts by vapor deposition. The coating prepared by the sol-gel method is prone to brittle cracking and peeling, and the preparation cycle is long. Cold spraying has a smaller heat output. In comparison, thermal spraying (TS) is efficient, low-cost and suitable for large-sized parts. It is a technology that rapidly heats the coating raw materials to a molten or molten state, and then makes the particles hit the substrate at high speed, and the molten droplets spread, solidify, and stack to form a coating. According to the type of heat source, it can be divided into flame spraying, supersonic flame spraying, arc spraying and plasma spraying. At present, there are three prominent problems in preparing ceramic thermal protection coatings on the surface of resin-based composite materials through thermal spraying technology. First, most of them use low-melting-point metals such as Zn and Al as the intermediate transition layer, which cannot guarantee electrical insulation. Second, high-temperature molten particles will have a strong ablation effect on the resin matrix, resulting in low layer-base bonding strength and easy peeling and failure during use. Third, the resin selected for the intermediate layer has low heat resistance and mechanical properties, which cannot meet the layer-base bonding characteristics of the composite coating.
[0004] Therefore, the preparation of a ceramic thermal protective coating that has both electrical insulation and ablation resistance on the surface of a low-melting-point resin-based composite material matrix is a practical method to improve the life and service reliability of the electromagnetic gun insulation support. Summary of the invention
[0005] In order to improve the technical problem that resin-based composite materials cannot have both electrical insulation and ablation resistance, the purpose of the present invention is to provide an epoxy resin surface alternately sprayed embedded composite coating and a preparation method. The composite coating prepared by this method takes into account both electrical insulation and ablation resistance, and can be better applied to harsh working conditions in the service environment.
[0006] In order to achieve the above objectives, the present invention adopts the following technical solutions to achieve the above objectives: A method for preparing an epoxy resin surface alternately sprayed embedded composite coating comprises the following steps: Thermoplastic polyimide powder, thermosetting polyimide powder, nano-alumina powder, deionized water and a binder are mixed to obtain a mixed material; The mixed materials are ball-milled and then spray-granulated to obtain polyimide-nano Al2O3 composite powder; Polyimide-nano Al2O3 composite powder and Al2O3 powder were sprayed alternately on the resin-based composite material by using wide-rate high-energy plasma spraying technology to obtain an epoxy resin surface alternately sprayed embedded composite coating.
[0007] Furthermore, the mass solid content of the mixture is 25%.
[0008] Furthermore, the mass of the binder is 1-3% of the mass of the mixed material, and the binder is polyvinyl alcohol or PEG.
[0009] Furthermore, the total mass fraction of thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina powder is 100, and the mass fraction ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina powder is (0-80): (80-0): 20, and the thermoplastic polyimide powder and the thermosetting polyimide powder cannot be 0 at the same time.
[0010] Furthermore, the particle size of the thermoplastic polyimide powder is 2-10 μm, the particle size of the thermosetting polyimide powder is 2-10 μm, and the particle size of the nano-alumina powder is 20-30 nm.
[0011] Furthermore, the resin-based composite material is pre-treated before spraying: the surface of the resin-based composite material is sandblasted and cleaned.
[0012] Furthermore, a wide-rate high-energy plasma spraying technique is used to alternately spray polyimide-nano Al2O3 composite powder and Al2O3 powder on the resin-based composite material, comprising the following steps: first spraying the polyimide-nano alumina composite powder one or more times, then spraying the Al2O3 powder one or more times, then spraying the polyimide-nano alumina composite powder one or more times, and finally spraying the Al2O3 powder one or more times.
[0013] Furthermore, during spraying, the polyimide-nano-alumina composite powder is fed into the jet by an external powder feeding method; and the Al2O3 powder is fed into the jet by an internal powder feeding method.
[0014] Furthermore, during spraying, the current is 380-420 A, the voltage is 80-90 V, the main gas is argon, and the argon gas flow rate is 60-65 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 10-14 L min -1 , the spraying distance is 150-180 mm, and the powder feeding distance of the composite powder is 90-110 mm.
[0015] The invention discloses an epoxy resin surface alternately sprayed embedded composite coating, wherein the composite coating has a maximum bonding strength of 20 MPa, a bending strength of 235 MPa after 150 ablation times, and a maximum resistivity of 71 TΩ·cm.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the process of preparing the composite coating, the present invention uses thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina as raw materials to form a polymer-ceramic composite coating, which can reduce the performance difference between the substrate and the ceramic layer, ensure the high reliability bonding of the coating, and reduce the ablation of the substrate. In the present invention, nano-alumina reinforcing filler is added to improve the mechanical properties of the nano-composite coating, such as bonding strength, plasma ablation resistance, and fracture strength. The steric hindrance effect of nano-alumina hinders the movement of macromolecular chains, effectively pins cracks, increases the crack propagation resistance, and improves the strength of the composite material. In the present invention, an alternating spraying method is adopted to optimize the composite coating structure and reduce the physical property difference between the coating and the substrate. At the same time, the cohesive bonding of the coating is effectively improved, and while meeting the high bonding characteristics of the coating, it also has both electrical insulation and ablation resistance, ensuring high reliability during the deposition process of the composite coating.
[0017] Furthermore, in the present invention, thermoplastic resin is added, and the ratio of thermoplastic and thermosetting resins in the composite powder is changed, wherein the excellent plasticity of thermoplastic polyimide significantly improves the bonding strength of the composite coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments; Figure 1 The microscopic morphology of the polyimide-nano-alumina composite powder prepared in Example 5 of the present invention; Figure 2 The microscopic morphology of the polymer-based nanocomposite coating prepared in Example 5 of the present invention; wherein, (a) is the overall morphology of the coating; (b) is the embedded morphology of the local alternately sprayed aluminum oxide; Figure 3 This is an optical photograph of the polymer-based nanocomposite coating prepared in Example 2-5 of the present invention after 150 plasma ablations; Figure 4 This is the stress-strain curve of the polymer-based nanocomposite coating prepared in Examples 2-5 of the present invention after 150 plasma ablations.
[0019] Figure 5 The resistivity of the polymer-based nanocomposite coatings prepared in Example 2 and Example 5 of the present invention. DETAILED DESCRIPTION
[0020] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0021] The present invention adopts glass fiber reinforced epoxy resin as a matrix and polyimide-nano Al2O3 as a composite coating. Polyimide has excellent mechanical properties, high thermal stability, corrosion resistance, and good electrical insulation. The addition of nanoparticles can improve the wear resistance, strength and thermal stability of polyimide composite materials. The nano Al2O3 particles dispersed in the coating limit the movement of molecular chains, resulting in enhanced nanocomposite behavior. High interfacial adhesion can effectively transfer the load from the polymer to the filler. Nano Al2O3 particles increase the crack propagation path, improve mechanical properties, and play a certain heat insulation role. The influence of the ratio of thermoplastic and thermosetting polyimide on the bonding strength of the coating is explored by adjusting the ratio.
[0022] The preparation method of the epoxy resin surface alternately sprayed embedded composite coating of the present invention comprises the following steps: (1) Preparation of polyimide (PI)-nano-Al2O3 composite powder: Mix thermoplastic polyimide powder, thermosetting polyimide powder, nano-alumina (Al2O3) powder, deionized water and binder, stir at 90 °C for 2 h to fully dissolve the binder in water, and obtain a mixture. The solid content (mass) of the mixture is 25%, and the mass of the binder is 1-3% of the mass of the mixture. The binder is polyvinyl alcohol or PEG. The total mass fraction of thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina powder is 100, and the mass fraction ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina powder is (0-80): (80-0): 20. Thermoplastic polyimide powder and thermosetting polyimide powder cannot be 0 at the same time. The mass ratio of thermoplastic and thermosetting polyimide is 3:7, 5:5, 7:3 or 10:0. The particle size of the thermoplastic polyimide powder is 2-10 μm, the particle size of the thermosetting polyimide powder is 2-10 μm, and the particle size of the nano alumina powder is 20-30 nm.
[0023] Then, the mixture was subjected to high-speed ball milling for 6-8 h using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was subjected to spray granulation at an air inlet temperature of 130 °C and a centrifugal speed of 300 Hz, and polyimide-nano-Al2O3 composite powder was obtained after drying.
[0024] (2) Pretreatment of the substrate before spraying: sandblasting and cleaning the surface of the resin-based composite material. The sandblasting material is aluminum oxide with a particle size of 120-180 μm, the sandblasting pressure is 0.3±0.05 MPa, the sandblasting angle is 70±10°, and the distance between the spray gun and the surface of the resin-based composite material is 100-150 mm. Use alcohol to clean the substrate surface.
[0025] (3) A composite coating is prepared on a resin-based composite material using a wide-range high-energy plasma spraying technique. The polyimide-nano alumina (Al2O3 / PI) composite coating and the Al2O3 coating are sprayed alternately. The specific process is: first spray the polyimide-nano alumina composite powder one or more times, then spray the Al2O3 powder one or more times, then spray the polyimide-nano alumina composite powder one or more times, and finally spray the Al2O3 powder one or more times. This reduces the physical property difference between the substrate and the alumina ceramic layer, ensures the high reliability of the coating, and finally covers the surface with a pure Al2O3 ceramic coating. By changing the number of spraying passes of the Al2O3 coating to optimize the optimal coating structure, the number of spraying passes is 1, 2 or 3, respectively, and finally the surface is covered with a pure Al2O3 ceramic coating, thereby obtaining an epoxy resin surface alternately sprayed embedded composite coating. Filling nano-Al2O3 particles into polyimide can improve the temperature resistance and mechanical properties of the nano-composite coating, reduce the difference in thermal expansion coefficients between the ceramic layer and the substrate, reduce thermal stress, and improve the bonding strength between the ceramic surface layer and the substrate.
[0026] The composite powder is fed into the jet by external powder feeding; the Al2O3 particles are fed into the jet by internal powder feeding. During spraying, the current is 380-420 A, the voltage is 80-90 V, the main gas is argon, and the argon gas flow rate is 60-65 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 10-14 L min -1 The spraying distance is 150-180 mm, and the powder feeding distance of the composite powder is 90-110 mm.
[0027] For resin-based composite materials, compressed air is added to the sample surface and back to cool them down to reduce the ablation and decomposition of the substrate and composite coating during the spraying process. Infrared temperature measuring devices are used to monitor the substrate surface temperature at 80-150 °C to prevent excessive temperatures.
[0028] The epoxy resin surface alternately sprayed embedded composite coating prepared by the above method of the present invention has a bonding strength that increases with the increase of the content of thermoplastic polyimide. When the mass content of nano-Al2O3 is 20% and the resin is all thermoplastic polyimide, the bonding strength is the highest, which is 20 MPa. When the number of spraying passes of the pure Al2O3 coating in the alternate spraying is gradually increased, ablation occurs in the nano-composite layer, and more cracks appear on the contact interface with the substrate, resulting in a decrease in the bonding strength of the coating. When the number of spraying passes of the pure Al2O3 coating in the alternate spraying is 1, the coating interface is well bonded, there is no ablation and decomposition phenomenon, and the aluminum oxide is embedded in the nano-composite layer, thereby improving the strength of the coating.
[0029] The following are specific embodiments.
[0030] Example 1 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an air inlet temperature of 130°C and a centrifugal rate of 300 Hz during spray granulation, and polyimide-nano-Al2O3 composite powder was obtained after drying. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 0:80:20.
[0031] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. The composite coating was prepared on the resin-based composite material by wide-speed high-energy plasma spraying technology, and the polyimide-nano Al2O3 composite coating and the Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and one coat of Al2O3 coating was sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and one coat of Al2O3 coating alternately, repeated twice, and finally three coats of pure Al2O3 coating were sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 380A, the voltage was 80 V, the main gas was argon, and the argon gas flow rate was 60L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 10 L min -1 The spraying distance was 150 mm, and the powder feeding distance of the composite powder was 90 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0032] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and the composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 80 °C to prevent the temperature from being too high.
[0033] Example 2 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an inlet air temperature of 130°C and a centrifugal rate of 300 Hz during spray granulation, and polyimide-nano-Al2O3 composite powder was obtained after drying. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 24:56:20.
[0034] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. The composite coating was prepared on the resin-based composite material by wide-range high-energy plasma spraying, and the polyimide-nano Al2O3 composite coating and the Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and one coat of Al2O3 coating was sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and one coat of Al2O3 coating alternately, repeated twice, and finally three coats of pure Al2O3 coating were sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 400A, the voltage was 85 V, the main gas was argon, and the argon gas flow rate was 62 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 12L min -1 The spraying distance was 160 mm, and the powder feeding distance of the composite powder was 100 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0035] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 100 °C to prevent the temperature from being too high.
[0036] Example 3 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an air inlet temperature of 130°C and a centrifugal rate of 300 Hz during the spray granulation. After drying, a polyimide-nano-Al2O3 composite powder was obtained. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 40:40:20.
[0037] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. The composite coating was prepared on the resin-based composite material by wide-range high-energy plasma spraying, and the polyimide-nano Al2O3 composite coating and the Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and one coat of Al2O3 coating was sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and one coat of Al2O3 coating alternately, repeated twice, and finally three coats of pure Al2O3 coating were sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 400A, the voltage was 85 V, the main gas was argon, and the argon gas flow rate was 62 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 12L min -1 The spraying distance was 160 mm, and the powder feeding distance of the composite powder was 100 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0038] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 100 °C to prevent the temperature from being too high.
[0039] Example 4 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an air inlet temperature of 130°C and a centrifugal rate of 300 Hz during spray granulation, and polyimide-nano-Al2O3 composite powder was obtained after drying. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 56:24:20.
[0040] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. The composite coating was prepared on the resin-based composite material by wide-range high-energy plasma spraying, and the polyimide-nano Al2O3 composite coating and the Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and one coat of Al2O3 coating was sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and one coat of Al2O3 coating alternately, repeated twice, and finally three coats of pure Al2O3 coating were sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 400A, the voltage was 85 V, the main gas was argon, and the argon gas flow rate was 62 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 12L min -1 The spraying distance was 160 mm, and the powder feeding distance of the composite powder was 100 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0041] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 120 °C to prevent the temperature from being too high.
[0042] Example 5 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an inlet air temperature of 130°C and a centrifugal rate of 300 Hz during spray granulation, and polyimide-nano-Al2O3 composite powder was obtained after drying. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 80:0:20.
[0043] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. A composite coating was prepared on the resin-based composite material by wide-range high-energy plasma spraying, and the polyimide-nano Al2O3 composite coating and the Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and one coat of Al2O3 coating was sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and one coat of Al2O3 coating alternately, repeated twice, and finally three coats of pure Al2O3 coating were sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 420A, the voltage was 90 V, the main gas was argon, and the argon gas flow rate was 65 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 14L min -1 The spraying distance was 180 mm, and the powder feeding distance of the composite powder was 110 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0044] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 150 °C to prevent the temperature from being too high.
[0045] from Figure 1 It can be seen that the composite powder prepared in Example 5 has a high sphericity and a particle size of 20-80 μm.
[0046] See also Figure 2 In (a) and (b), from Figure 2 It can be seen that in the prepared coating, alumina is embedded in the polyimide-nano alumina composite coating, the interface bonding is good, and the alumina coating is pinned, which ensures the high bonding strength of the composite coating. See also Figure 3 This is the plasma ablation morphology of Example 2-5, wherein the plasma ablation uses a wide-speed high-energy plasma jet to ablate the coating surface, and the ablation power is 40 kW.
[0047] See also Figure 4 Through the three-point bending mechanical property test, the bending strengths of Examples 2-5 were 210 MPa, 220 MPa, 225 MPa, and 235 MPa, respectively. Compared with the pure matrix, the bending strength of the sample with a plastic:solid ratio of 3:7 after 150 ablation was 235 MPa, which was increased by 28%.
[0048] See also Figure 5 Through the resistivity test, the coatings of Example 2 and Example 5 are higher than the pure substrate, and the resistivities of the samples with plastic:solid ratios of 10:0 and 3:7 are 71 TΩ·cm and 51 TΩ·cm, respectively.
[0049] Example 6 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an inlet air temperature of 130°C and a centrifugal rate of 300 Hz during spray granulation, and polyimide-nano-Al2O3 composite powder was obtained after drying. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 80:0:20.
[0050] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. A composite coating was prepared on the resin-based composite material by wide-range high-energy plasma spraying, and polyimide-nano Al2O3 composite coating and Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and two coats of Al2O3 coating were sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and two coats of Al2O3 coating alternately, repeated twice, and finally two coats of pure Al2O3 coating were sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 420A, the voltage was 90 V, the main gas was argon, and the argon gas flow rate was 65 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 14L min -1 The spraying distance was 180 mm, and the powder feeding distance of the composite powder was 110 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0051] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 150 °C to prevent the temperature from being too high.
[0052] Example 7 Thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder were mixed with deionized water and a binder. The solid content was 25% and the binder content was 1%. The mixture was milled at high speed using a planetary ball mill to obtain a uniformly dispersed slurry. The uniformly dispersed slurry was spray granulated at an inlet air temperature of 130°C and a centrifugal rate of 300 Hz during spray granulation, and polyimide-nano-Al2O3 composite powder was obtained after drying. Among them, the mass ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-Al2O3 powder was 80:0:20.
[0053] The substrate was pretreated before spraying: the surface of the resin-based composite material was sandblasted and cleaned. A composite coating was prepared on the resin-based composite material by wide-range high-energy plasma spraying, and polyimide-nano Al2O3 composite coating and Al2O3 coating were sprayed alternately. Two coats of polyimide-nano Al2O3 composite powder were used as the primer, and three coats of Al2O3 coating were sprayed, followed by one coat of polyimide-nano Al2O3 composite powder and three coats of Al2O3 coating alternately, repeated twice, and finally one coat of pure Al2O3 coating was sprayed on the surface. The composite powder was fed into the jet by external powder feeding; the Al2O3 particles were fed into the jet by internal powder feeding. During spraying, the current was 420A, the voltage was 90 V, the main gas was argon, and the argon gas flow rate was 65 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 14L min -1 The spraying distance was 180 mm, and the powder feeding distance of the composite powder was 110 mm, and an epoxy resin surface alternately sprayed embedded composite coating was obtained.
[0054] The resin-based composite material is cooled front and back to reduce the ablation and decomposition of the substrate and composite coating during the spraying process, and an infrared temperature measuring device is used to monitor the substrate surface temperature at 150 °C to prevent the temperature from being too high.
[0055] The bonding strengths of the polymer-based nanocomposite coatings prepared in different proportions according to the present invention are shown in Table 1.
[0056] Table 1 Bonding strength of polymer-based nanocomposite coatings of different proportions prepared by the present invention
[0057] See Table 1. It can be seen from Table 1 that with the increase of the content of thermoplastic polyimide, the bonding strength of the coating increases. The bonding strength of the coating is the highest when it is pure thermoplastic resin, reaching 20 MPa. When the number of times of spraying Al2O3 powder alternately increases to 2 and 3, cracks will appear in the coating due to ablation, resulting in a decrease in bonding strength. When the number of times of spraying Al2O3 powder alternately is 1, the bonding strength is the best. Compared with the pure substrate, the flexural strength is 235 MPa after 150 ablation times, which is 28% higher, and it shows excellent resistance to plasma ablation.
[0058] In the present invention, nano-Al2O3 particles are filled into polyimide to improve the temperature resistance and mechanical properties of the nano-composite coating, reduce the difference in thermal expansion coefficients between the ceramic layer and the substrate, reduce thermal stress, and improve the bonding strength between the ceramic surface layer and the substrate. The polyimide-nano-Al2O3 composite material is introduced as a transition layer of the composite coating to ensure high bonding between the glass fiber reinforced resin-based composite material and the alumina ceramic layer, and improve the temperature resistance and wear resistance of the substrate. Alumina is embedded in the polymer-based nano-composite coating, and the interface bonding is good.
[0059] The present invention adopts glass fiber reinforced epoxy resin with low density and high specific strength as the matrix. By introducing a polymer-ceramic composite coating, the performance difference between the matrix and the ceramic layer can be reduced, the high reliability combination of the coating can be ensured, the thermal stability and wear resistance of the polymer composite material can be improved, and its performance can be further improved. The polyimide-nano Al2O3 with excellent comprehensive performance is used as a transition coating. Compared with the traditional microstructure composite coating, the nano composite coating shows excellent characteristics in mechanical properties such as hardness, elastic modulus, fracture toughness and bonding strength. The addition of nanoparticles can improve the wear resistance, strength and thermal stability of the polyimide composite material. The nano Al2O3 particles dispersed in the composite coating limit the movement of the molecular chain, resulting in enhanced nano composite behavior, high interface adhesion can effectively transfer the load from the polymer to the filler, and the nano Al2O3 particles increase the crack propagation path, improve the mechanical properties, and play a certain heat insulation role. The influence of the ratio of thermoplastic and thermosetting polyimide on the bonding strength of the coating is explored by adjusting the ratio.
[0060] The present invention optimizes the structure of the coating by adjusting the ratio of thermoplastic and thermosetting polyimide, changing the number of spraying times of Al2O3 powder in the alternating spraying process, obtaining the component ratio of the composite powder and the number of spraying times of the Al2O3 powder when the bonding strength is high, exploring the intrinsic relationship between the microstructure and the mechanical properties, and having the characteristics of simple operation process, good repeatability, significant economic benefits and accurate and reliable results. In the prepared composite coating, alumina is embedded in the polyimide-nano alumina composite coating, showing high bonding strength.
[0061] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing an epoxy resin surface alternately sprayed embedded composite coating, characterized in that: The following steps are involved: Thermoplastic polyimide powder, thermosetting polyimide powder, nano-alumina powder, deionized water and a binder are mixed to obtain a mixed material; The mixed materials are ball-milled and then spray-granulated to obtain polyimide-nano Al2O3 composite powder; Polyimide-nano Al2O3 composite powder and Al2O3 powder were sprayed alternately on the resin-based composite material by using wide-rate high-energy plasma spraying technology to obtain an epoxy resin surface alternately sprayed embedded composite coating.
2. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: The mass solid content of the mixture is 25%.
3. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: The mass of the binder is 1-3% of the mass of the mixed material, and the binder is polyvinyl alcohol or PEG.
4. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: The total mass fraction of thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina powder is 100, and the mass fraction ratio of thermoplastic polyimide powder, thermosetting polyimide powder and nano-alumina powder is (0-80): (80-0):
20. Thermoplastic polyimide powder and thermosetting polyimide powder cannot be 0 at the same time.
5. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: The particle size of the thermoplastic polyimide powder is 2-10 μm, the particle size of the thermosetting polyimide powder is 2-10 μm, and the particle size of the nano alumina powder is 20-30 nm.
6. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: Pretreatment of the resin-based composite material before spraying: sandblasting and cleaning of the surface of the resin-based composite material.
7. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: The invention adopts a wide-speed high-energy plasma spraying technology to alternately spray polyimide-nano Al2O3 composite powder and Al2O3 powder on a resin-based composite material, comprising the following steps: first spraying the polyimide-nano alumina composite powder one or more times, then spraying the Al2O3 powder one or more times, then spraying the polyimide-nano alumina composite powder one or more times, and finally spraying the Al2O3 powder one or more times.
8. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: During spraying, the polyimide-nano-alumina composite powder is fed into the jet by an external powder feeding method; and the Al2O3 powder is fed into the jet by an internal powder feeding method.
9. The method for preparing the epoxy resin surface alternately sprayed embedded composite coating according to claim 1, characterized in that: During spraying, the current is 380-420 A, the voltage is 80-90 V, the main gas is argon, and the argon gas flow rate is 60-65 L min -1 , the secondary gas is hydrogen, and the hydrogen gas flow rate is 10-14 L min -1 , the spraying distance is 150-180 mm, and the powder feeding distance of the composite powder is 90-110 mm.
10. An epoxy resin surface alternately sprayed embedded composite coating prepared according to the method of any one of claims 1 to 9, characterized in that: The composite coating has a maximum bonding strength of 20 MPa, a bending strength of 235 MPa after 150 ablation cycles, and a maximum resistivity of 71 TΩ·cm.
Citation Information
Patent Citations
Insulating composite paint of nanometer inorganic matter and polymer and its prepn
CN101020800A
Method utilizing thermal spraying technique for preparing polyimide coating and product of method
CN105903650A
Preparation method and device of composite coating for resin-based composite material
CN114950919A
Multi-layer corrosion resistant coatings
US6342272B1